One-Pot Sequential 1,4- and 1,2-Reductions of α,β-Unsaturated δ-Lactones to the Corresponding δ-Lactols with CuCl and NaBH4 in Methanol - Matsumoto, Yasunobu; Yonaga, Masahiro (Synlett, 2014)
An efficient, one-pot method for the highly chemoselective synthesis of δ-lactols from α,β-unsaturated δ-lactones using CuCl and NaBH4 in methanol was developed.
Keywords: copper; hydrides; lactones; lactols; reduction